2022
DOI: 10.1177/21514593221098620
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Validation of a Nomogram for the Risk of New Vertebral Compression Fractures After Percutaneous Vertebroplasty in Patients With Osteoporotic Vertebral Compression Fractures: A Retrospective Study

Abstract: Purpose New vertebral compression fractures(NVCFs) after minimally invasive surgery in patients with osteoporotic vertebral compression fracture (OVCF) is a challenging issue worldwide. Predicting the occurrence of NVCFs is key to addressing such questions. Therefore, we aimed to investigate the risk factors for patients who developed NVCFs after undergoing surgical treatment and establish a nomogram model to reduce the occurrence of NVCFs. Methods This study is a retrospective analysis that collected the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Recently, researchers developed predictive models for NVCF after OVCF [ 25 28 ]. A recent retrospective study by Bian et al found that 23.8% (69/292) of patients develop NVCF after PVP surgery, and they found four independent risk factors, including age, HU value, cement leakage, and thoracolumbar junction fracture, could predict NVCF [ 26 ]. Li et al found that 15.1% (58/385) of OVCF patients develop NVCF after PVP surgery, and, they found that higher BMI, lower BMD, multisegment vertebral fractures, no previous anti-osteoporosis treatment, and steroid use were more likely to result in NVCF after PVP surgery [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers developed predictive models for NVCF after OVCF [ 25 28 ]. A recent retrospective study by Bian et al found that 23.8% (69/292) of patients develop NVCF after PVP surgery, and they found four independent risk factors, including age, HU value, cement leakage, and thoracolumbar junction fracture, could predict NVCF [ 26 ]. Li et al found that 15.1% (58/385) of OVCF patients develop NVCF after PVP surgery, and, they found that higher BMI, lower BMD, multisegment vertebral fractures, no previous anti-osteoporosis treatment, and steroid use were more likely to result in NVCF after PVP surgery [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bian et al. ( 26 ) concluded that age, HU value, TL junction fracture, and cement leakage were correlated with new VCF after PVP in patients with OVCF. In this study, only a low HU value was the independent risk factor of new VCF after PVP or PKP by multivariate regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Ning et al (25) reported that risk factors of new VCF after PKP for OVCF were gender, zoledronic acid, and previous fracture history rather than BMI, smoking, alcohol, hypertension, and diabetes. Bian et al (26) concluded that age, HU value, TL junction fracture, and cement leakage were correlated with new VCF after PVP in patients with OVCF. In this study, only a low HU value was the independent risk factor of new VCF after PVP or PKP by multivariate regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The L3 vertebrae average Hounsfield Unit (HU) value was calculated as follows: the vertebral body was divided into 3 equal parts in the sagittal plane, and the largest elliptical region of interest (ROI) containing only bone trabeculae was drawn in the axial plane to obtain the average CT value, avoiding the cortical bone and posterior venous plexus 4 ( Figure 1 A).…”
Section: Methodsmentioning
confidence: 99%